Language Production of Children Aged 3-4 Years in Working and Non-Working Parents in Kalikapas Hamlet, Lamongan Regency: A Psycholinguistic Study - Agustiansyah Amanda; Mintowati; Agusniar Dian Savitri; Ratih Kirana Suryo Puteri (Universitas Negeri Semarang, 2025)
The role of parents is crucial in determining a child's ability to produce speech and develop vocabulary. Socioeconomic changes and parental involvement in work have led to a decrease in the intensity of communication, which has the potential to hinder children's language acquisition and social interaction. This study aims to describe the differences in language production abilities among children aged 3–4 years in Kalikapas Hamlet, Lamongan Regency, between those whose parents are employed and those whose parents are not employed. The research employed a descriptive qualitative approach, utilizing data collection techniques that included observation and in-depth interviews with 11 informants. The data were analysed through transcription, speech classification, and social context interpretation with triangulation of sources. The study's results indicate that there are differences in the language production abilities of children from working and non-working families. Children of non-working parents demonstrate better phonological and syntactic skills, can form complex sentences with subject-predicate-object-adverbial structures, and have more precise pronunciation. The study's results indicate that there are differences in the language production abilities of children from households with working and non-working parents. Children of non-working parents demonstrate better phonological and syntactic skills, can form complex sentences with subject-predicate-object-complement structures, and have more precise pronunciation. The results also show that children of working parents tend to have limitations in phoneme pronunciation and simple sentence construction due to lower intensity of interaction. These findings confirm that the frequency and quality of two-way conversations between children and parents play a crucial role in children's language development. A home environment rich in verbal stimulation and simple literacy activities, such as storytelling and reading together, has been shown to support the improvement of children's vocabulary and syntactic structure.